Yeasts in nanotechnology-enabled oral vaccine and gene delivery. Issue 1 (1st January 2021) - Ivanova, Elena
ABSTRACT: Oral vaccine and gene delivery systems must be engineered to withstand several different physiological environments, such as those present in the oral cavity, stomach, and jejunum, each of which exhibits varying pH levels and enzyme distributions. Additionally, these systems must be designed to ensure appropriate gastrointestinal absorption and tissue/cellular targeting properties. Yeasts-based delivery vehicles are excellent candidates for oral vaccine and oral gene therapies as many species possess cellular characteristics resulting in enhanced resistance to the harsh gastrointestinal (GI) environment and facilitated passage across the mucosal barrier. Yeast capsules can stimulate and modulate host immune responses, which is beneficial for vaccine efficacy. In addition, recombinant modification of yeasts to express cell penetrating proteins and injection mechanisms along with efficient cell adhering capabilities can potentially improve transfection rates of genetic material. In this literature review, we present evidence supporting the beneficial role yeast-based delivery systems can play in increasing the efficacy of oral administration of vaccines and gene therapies.